FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BELI MASYARAKAT KECAMATAN MATANGKULI TERHADAP PRODUK MEREK PRIBADI ALFAMART - Ratna Auliana; Ismaulina Ismaulina (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2017)
Alfamart's personal brand is a foreign matter, where few people know about Alfamart's personal brand products. The lack of public knowledge about Alfamart's personal brand products will certainly have an impact on people's buying interest in these products. The formulation of the problem in this study are: What products use Alfamart's personal brand and what factors influence the people's buying interest in Matangkuli District on alfamart's personal brand products ?. The research method used is a quantitative method using a Likert scale, namely obtaining data through questionnaires in the field and the data analyzed through the SPSS Window 22 program. The results of the study are: Products that use Alfamart's personal brand, namely: Food Products, Beverage Products, Repeat Equipment Year, as well as other products. Based on the results of the research both in the t test (partial test) and F test (simultaneous test), there is no single factor that influences the buying interest of the people in the Matangkuli sub-district towards Alfamart's personal brand products.